Bahasa Willy sebagai Penanda Komunitas Gaul-Jamet di Media Sosial X (Twitter): Tinjauan Morfosintaksis - Salamah, Salamah; Muttaqin, Syariful; Sugiharyanti, Eni (Deskripsi Bahasa, 2025)
This study aimed at mapping the morphological changes, functions, categories, syntactic roles, and linguistic tendencies in Willy language. This research employed a descriptive-qualitative method incorporated by the morphosyntax approach. Data were collected through document study techniques. The analysis focused on 23 sentences from Willy language, a colloquial form used by ‘jamet’ speakers on X (Twitter). The findings showed that the morphological changes include prefix modification, syllable reduction, spelling deviation, abbreviation, and sound alteration. Most sentences performed an inversion pattern, where the predicate precedes the subject (P-S), with a predominance of simple sentences. The writing style resembled that of a drama script, leading to a hierarchical structure. A few coordinate compound sentences were also identified. The main word categories include nouns, verbs, and adverbs, with a notable presence of phatic expressions and interjections. The predominant roles observed were agentive, activity, object (sufferer), and instrument/manner. Overall, the linguistic patterns indicate: (1) dominance of inverted and simple sentences; (2) a majority of noun, verb, and adverb classes; (3) scarcity of conjunctions and adjectives; (4) minimal use of prepositions; (5) inclusion of phatic expressions, interjections, and onomatopoeia; (6) a writing style similar to drama scripts; and (7) phonological and morphological transformations.